Understanding Career Maturity in Adolescents: Examining the Predictive Model of Social Intelligence and Self-Efficacy - Novita Maulidya Jalal; Dwi Yan Nugraha (Humanitas: Indonesian Psychological Journal, 2026)
This study aims to examine the predictive roles of social intelligence and self-efficacy in adolescents’ career maturity. The participants were 89 adolescents in Makassar City, ranging from secondary to higher education levels, selected through purposive random sampling. Data were collected using standardised measures of social intelligence, self-efficacy, and career maturity. Multiple hierarchical regression analysis using the R programming language was conducted to test the hypothesised model. The results revealed that self-efficacy significantly predicted career maturity, while social intelligence contributed indirectly by enhancing self-efficacy, which in turn supported adolescents’ career development. These findings emphasise that strengthening self-belief through mastery experiences and positive reinforcement plays a more crucial role in shaping career maturity, whereas social intelligence facilitates interpersonal understanding and adaptive social interactions that indirectly foster self-efficacy. The study suggests that interventions combining self-efficacy enhancement with social intelligence training could be an effective strategy to support adolescents in achieving their career goals. Although the sample size was relatively modest, a supplementary Monte Carlo simulation demonstrated sufficient statistical power and model sensitivity to support the robustness of these findings